Teacher’s Ridha In The Ethics Of Santri Khidmah: A Hermeneutic Phenomenological Study On Pesantren’s Cultural Resistance To “Santri Slavery” Narratives In Digital Public Spaces - Warsah, Idi; Morganna, Ruly; Warsah, Berliani Aslam Alkiromah; Warsah, Bizikrika Hably Hudaya (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The issue of “santri slavery” that has circulated widely on social media has distorted the meaning of pesantren education by framing the teacher–student relationship through a paradigm of power rather than spirituality. This narration obscures the moral values underlying the traditional Islamic educational system and has generated public misunderstanding of the practice of devotion (khidmah). This study phenomenologically examines the concept of teacher’s ridha as both the moral foundation of Islamic educational ethics and a form of cultural resistance against accusations of exploitation in modern public discourse. Employing a qualitative approach with a hermeneutic phenomenological design, the research was conducted in three traditional pesantren in East Java, involving 10 active students (santri), 4 teachers (ustaz), and 3 alumni as the participants. Data were collected through in-depth interviews, participatory observation, and focus group discussions (FGD), and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that teacher’s ridha serves as a value structure that governs the teacher–student relationship within a framework of compassion and moral responsibility rather than hierarchical domination. The practice of khidmah is understood as a form of experiential learning that cultivates sincerity, patience, and spiritual character formation. At the same time, the value of teacher’s ridha functions as a moral and symbolic mechanism of resistance to exploitation narratives by redefining devotion as an expression of inner freedom. Furthermore, pesantren have begun utilizing digital media to disseminate alternative narratives grounded in spirituality and adab (ethical conduct). Theoretically, teacher’s ridha is not merely an ethical value but also an epistemological mechanism in the formation of moral subjects, offering an alternative framework to secular paradigms by integrating spiritual legitimacy, exemplary conduct, and lived sincerity. Thus, teacher’s ridha operates as an authentic symbol of liberating Islamic education and as a form of cultural capital that enables pesantren to sustain their moral integrity amid the pressures of modernity.